A transient benign lymph node-based proliferation of T-cells simulating non-Hodgkin lymphoma in a patient with psoriasis treated with tumor necrosis factor alpha and CD11a antagonists - Leonardi Craig L; George Mary; Hurley M Yadira; Frater John L (BMC, 2008)
Abstract Background Therapeutic biologic agents are uncommonly associated with lymphoma. Case presentation We report a patient with psoriasis treated with the biologic agents efalizumab (Raptiva®) and etanercept (Enbrel®), who developed painless lymphadenopathy with peripheral lymphocytosis during treatment, simulating a non-Hodgkin lymphoma clinically and pathologically. Lymphocytosis and lymphadenopathy spontaneously remitted following cessation of etanercept therapy and have not recurred. Conclusion Distinction between clinically benign lymphoid proliferations related to antipsoriasis therapy and malignant lymphoma avoids the unnecessary use of anti-lymphoma chemotherapy.